Towards Reduction: Exploring the links between Oneness and Fashion Consumption - Areias, Salomé Pimentel (2025)
In the 15 years preceding the Paris Agreement, global garment production doubled from 50 billion to a hundred billion pieces per year, despite the world population comprising only 7% of that figure. Over the following six years, consumption surged at an unprecedented rate, surpassing 75% of all resources used throughout the 20th century. Despite efforts to curb overconsumption through reuse and repair policies, these initiatives often encourage the production of more durable and life-extendable products that are still ultimately destined to landfills, if governments keep overlooking the subconscious triggers of consumerism that remain embedded and profitable in market systems. The growing environmental and psychological impact of consumerism and fashionables has prompted growing research into alternative approaches within environmental science. One such emerging perspective is oneness, a concept reclaimed from psychoanalysis and ancient mystical traditions and now gaining attention in environmental psychology. Oneness describes an ineffable reality where all existence is fundamentally one and thus underscores an important perception about the self – it transcends the individual to include everything else (i.e., others, living beings, nature, the universe), which might involve a profound sense of collective self-protection in the midst of climate emergency. This research identifies the potential of oneness as a driver of consumption reduction, unveiled by oneness’ positive correlation with pro-environmental behaviour as well as with other variables suggesting a realignment with a foundational truth or essential well-being. The aim of this research is to examine the predictive potential of oneness in fostering consumption reduction, particularly in fashion, due to its close links to impulsive buying and self-identity construction. A mixed-method approach integrates a semi-systematic literature review with a keyword search relating interconnectedness, sense of self, environment, and consumption; an implicit association test (IAT) on oneness combined with semi-structured expert interviews; and a social experiment tracking consumer behaviour at a clothing market stall. Predictive modelling in R analyses correlations between oneness IAT scores and purchasing behaviour, exploring interactions with voluntary simplicity and sustainable consumption scales. The literature review showed that all identified linkages between a deep integration of self in unity with an ‘other’ and pro-environmental consumption were found to be positive. It is also positively linked to mindful practices defined by high states of awareness. Further exploration in review revealed that environmentally responsible consumption is often driven by guilt, which can paradoxically trigger denial, suppression of political claims, and engagement in hazardous consumption patterns. The novel assessment tool on oneness, developed in this research with input from expert interviews, showed valid results in the pilot-test. The implicit association test demonstrated content validity, construct validity, criterion-related validity, and internal consistency reliability, according to the psychometric analysis it underwent. The market experiment revealed a marginal yet inconclusive negative correlation between oneness and buying behaviour, suggesting that participants with higher oneness IAT scores were slightly less likely to engage in purchases. This work discusses the measurability of oneness, future methodological refinements, and practical applications of findings, emphasizing the need to honour the radical and mystical nature of oneness in recognizing its transformative potential within inner and collective worlds.